Mashlahah's Perspective on Two Marriage Contracts for Children Out of Wedlock - Muhammad Alawy Rangkuti; Hasan Matsum; Dhiauddin Tanjung (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to examine the practice of two marriage contracts for illegitimate daughters in Deli Serdang Regency from the perspective of mashlahah. This study uses a qualitative approach with a descriptive analytical method through interviews, observations, and documentation. The study results indicate that the first contract carried out by the guardian judge is legally valid under Islamic law because it fulfills the pillars and requirements of marriage. In contrast, the second contract carried out by the biological father is only symbolic and has no legal force. Implementing the second contract is intended to maintain the honor of the family and cover up past disgrace, so it is seen as a form of mashlahah mursalah that is tolerated as long as it does not conflict with the basic principles of sharia. Therefore, this phenomenon reflects a social need that demands a wise, contextual, and community-oriented Islamic legal approach